THE PROBLEMATIC ASPECTS OF THE RENEWABLE ENERGY PROMOTION LEGAL REGULATION - Poderis, Justinas (Teisė, 2016)
The key aim of the renewable energy promotion is to satisfy public interests. In accordance with the Lithuanian laws, renewable energy regulation is based on long-term, fixed promotion of the renewable energy development which directly correlates to electricity price. Due to the continues nature of the renewable energy promotion legal regulation, the changes of the feed-in tariffs applicable for the future purchase of the electricity shall be recognised as compatible with lex retro non agit principle. Economically reasonable electricity price for the consumers and intensive development of the renewable energy are the main public interests competing in the renewable energy promotion sector. Problems of intersection of these principles shall be solved in accordance with the coordination of the different interests’ principle ensuring renewable energy promotion consistency, economic feasibility of the development of the renewable energy projects and a temperate influence of such development on electricity price.